Static plantar pressure and functional capacity in children with femoral shaft fractures treated by titanium elastic nailing - Elena Amăricăi; Oana Suciu; Roxana Ramona Onofrei; Emil Radu Iacob; Daniela Iacob; Călin Marius Popoiu; Marius Negru; Oana Belei; Luminița Bădițoiu; Eugen Boia (BMC Musculoskeletal Disorders, 2019)
Abstract Background Femoral shaft fractures represent common fractures of the lower limb in the paediatric population. The objectives of our study were to analyse the static plantar pressure and functional capacity in children with surgically treated unilateral femoral shaft fractures, 1 month after the metallic implant removal. Methods Our study included 24 children with unilateral femoral shaft fracture (fracture site contralateral to the dominant leg) treated by titanium elastic nailing (TEN) implants, with the removal of the implant 6 months after initial surgery. The patients were divided into two groups: Group 1 (12 patients without inpatient rehabilitation) and Group 2 (12 patients who attended inpatient rehabilitation). The patients and 12 gender and age-matched healthy controls performed plantar pressure analysis and functional capacity testing (6-min walk test: 6MWT). For patients in Group 1 and 2 the assessments were performed 1 month after the TEN implant removal. Paired t-tests were used to compare the intragroup data. A one-way ANOVA test for independent measures was performed to assess the differences for plantar pressure, and 6MWT among study groups and controls. Results All study patients had left femoral shaft fractures (affected limb). The patients and controls were all right leg dominant. In both Group 1 and Group 2 total foot loading was significantly higher on the non-affected limb compared with the affected limb. When compared to the non-affected limb, the loadings on the affected limb were significantly increased on the first and fifth metatarsal in Group 1, and on the fifth metatarsal in Group 2, with a significantly smaller heel loading. When compared with the controls we found significant differences for all pressure parameters, except for the right foot load for the rehabilitation group. Although the functional capacity values were higher in the rehabilitation group the two patients groups had significantly lower 6MWT values. Conclusions When compared to healthy controls children with surgically treated unilateral femoral shaft fractures, although assessed after 7 months, had a different weight distribution on the feet and a decreased functional capacity. A rehabilitation programme included in the management of these patients is important for regaining their functional level.